413 GEN-009, a personalized neoantigen vaccine, elicits robust immune responses in individuals with advanced or metastatic solid tumors. (9th November 2020) - Shainheit, Mara; Champagne, Devin; Santone, Gabriella; Shukor, Syukri; Bicak, Ece; Tipps, Samuel; Xue, Li; Davis, Thomas; Flechtner, Jessica
Abstract : Background: ATLAS TM is a cell-based bioassay that utilizes a cancer patient's own monocyte-derived dendritic cells and CD4 + and CD8 + T cells to screen their mutanome and identify neoantigens that elicit robust anti-tumor T cell responses, as well as, deleterious InhibigensTM. 1 GEN-009, a personalized vaccine comprised of 4–20 ATLAS-identified neoantigens combined with Hiltonol®, harnesses the power of neoantigen-specific T cells to treat individuals with solid tumors. The safety and efficacy of GEN-009 is being assessed in a phase 1/2a clinical trial (NCT03633110 ). Methods: A cohort of 15 adults with solid tumors were enrolled in the study. During the screening period, patients received standard of care PD-1-based immunotherapies appropriate for their tumor type. Subsequently, patients were immunized with GEN-009 with additional doses administered at 3, 6, 12, and 24 weeks. Peripheral blood mononuclear cells (PBMCs) were collected at baseline, pre-vaccination (D1), as well as 29, 50, 92, and 176 days post first dose. Vaccine-induced immunogenicity and persistence were assessed by quantifying neoantigen-specific T cell responses in ex vivo and in vitro stimulation dual-analyte fluorospot assays. Polyfunctionality of neoantigen-specific T cells was evaluated by intracellular cytokine staining. Additionally, potential correlations between the ATLAS-identified profile and vaccine-induced immunogenicity were assessed. Results: GEN-009 augmented T cell responses in 100% of evaluated patients, attributable to vaccine and not checkpoint blockade. Furthermore, neoantigen-induced secretion of IFNγ and/or TNFα by PBMCs, CD4 +, and CD8 + T cells was observed in all patients. Responses were primarily from polyfunctional TEM cells and detectable in both CD4 + and CD8 + T cell subsets. Some patients had evidence of epitope spreading. Unique response patterns were observed for each patient with no apparent relationship between tumor types and time to emergence, magnitude or persistence of response. Ex vivo vaccine-induced immune responses were observed as early as 1 month, and in some cases, persisted for 176 days. Clinical efficacy possibly attributable to GEN-009 was observed in several patients, but no correlation has yet been identified with neoantigen number or magnitude of immune response. Conclusions: ATLAS empirically identifies stimulatory neoantigens using the patient's own immune cells. GEN-009, which is comprised of personalized, ATLAS-identified neoantigens, elicits early, long-lasting and polyfunctional neoantigen-specific CD4 + and CD8 + T cell responses in individuals with advanced cancer. Several patients achieved clinical responses that were possibly attributable to vaccine; efforts are underway to explore T cell correlates of protection. These data support that GEN-009, in combination with checkpoint blockade, represents a unique approach to treat solid tumors. Acknowledgements: We are grateful to the patients and their families who consented to participate in the GEN-009-101 clinical trial. Trial Registration: NCT03633110 Ethics Approval: This study was approved by Western Institutional Review Board, approval number 1-1078861-1. All subjects contributing samples provided signed individual informed consent. Reference: DeVault V, Starobinets H, Adhikari S, Singh S, Rinaldi S, Classon B, Flechtner J, Lam H. Inhibigens, personal neoantigens that drive suppressive T cell responses, abrogate protection of therapeutic anti-tumor vaccines. J. Immunol 2020; 204(1 Supplement):91.15.